Pengaruh Penghambatan Kebeningan Kaca Terhadap Kemampuan Transfer Intensitas Cahaya Pada Kaca - Muhammad Sayuthi; Ahmad Syuhada; M. Nizar Machmud (Jurnal Teknik Mesin Unsyiah, 2014)
The sun is the primary source of energy on the earth, but its light sometimes cause thermal discomfort for humans. The thermal engineering started one in the automotive sector in particular car is to install the air conditioner to lower the temperature of the cabin and use the tranfer window film to block sun light intensity. Testing the proper use of window film to determine the effect of inhibition of the ability to transfer the glass clarity of light intensity on the glass needs to be done to determine what percentage inhibition that has the intensity and the lower the cabin temperature, so the thermal comfort is achieved faster. From the results of the testing were conditioned using Solar ray Collector © PHYWE Systeme GmbH CO.KG. Inhibition obtained with 40% glass has an intensity of 39% and a temperature of 63.20 C, the glass has an intensity of 60% inhibition of 21% and a temperature of 61.90 C, the glass has an intensity of 80% inhibition of 8% and a temperature of 63.80 C. So the use of glass with 60% inhibition is best to accelerate the thermal comfort is achieved.